Notes and observations on Tofieldia glutinosa. - Snyder, Andre (1996)
Tofieldia glutinosa, a charismatic member of the Liliaceae family generically known as the False Asphodel, is a slender, sticky-stemmed perennial found throughout northern North America, including the Great Lakes region, central New York, the Appalachian mountains (from West Virginia south to Georgia) of the eastern United States, and from Manitoba to Newfoundland in Canada. http://deepblue.lib.umich.edu/bitstream/2027.42/54696/1/3137.pdf Description of 3137.pdf : Access restricted to on-site users at the U-M Biological Station.